Importance of mineral nutrition for mitigating aluminum toxicity in plants on acidic soils: Current status and opportunities - Rahman, M.A.; Lee, S.H.; Ji, H.C.; Kabir, A.H.; Jones, Christopher S.; Lee, K.W. (MDPI, 2018)
Aluminum (Al) toxicity is one of the major limitations that inhibit plant growth and development in acidic soils. In acidic soils (pH < 5.0), phototoxic-aluminum (Al3+) rapidly inhibits root growth, and subsequently affects water and nutrient uptake in plants. This review updates the existing knowledge concerning the role of mineral nutrition for alleviating Al toxicity in plants to acid soils. Here, we explored phosphorus (P) is more beneficial in plants under P-deficient, and Al toxic conditions. Exogenous P addition increased root respiration, plant growth, chlorophyll content, and dry matter yield. Calcium (Ca) amendment (liming) is effective for correcting soil acidity, and for alleviating Al toxicity. Magnesium (Mg) is able to prevent Al migration through the cytosolic plasma membrane in root tips. Sulfur (S) is recognized as a versatile element that alleviates several metals toxicity including Al. Moreover, silicon (Si), and other components such as industrial byproducts, hormones, organic acids, polyamines, biofertilizers, and biochars played promising roles for mitigating Al toxicity in plants. Furthermore, this review provides a comprehensive understanding of several new methods and low-cost effective strategies relevant to the exogenous application of mineral nutrition on Al toxicity mitigation. This information would be effective for further improvement of crop plants in acid soils.